Non-invasive soft breakdown localisation in low k dielectrics using photon emission microscopy and thermal laser stimulation. (January 2019) - Herfurth, N.; Wu, C.; Beyreuther, A.; Nakamura, T.; De Wolf, I.; Simon-Najasek, M.; Altmann, F.; Croes, K.; Boit, C.
Abstract: For the first time a non-invasive localisation of a soft breakdown (SBD) is shown. The localisation is completed on fully functional back end of line (BEOL) test structures. The test structures used, provided by the interuniversity microelectronics centre (imec), are metal insulator semiconductor (MIS) structures. The low k dielectric within the test structures is SiOCH type with OSG 2.0 (k = 2.0), 45% porosity and 40 nm thickness. Contacless faul isolation methods have been evaluated for detecting a SBD on these structures. We evaluated photon emission microscopy (PEM) with two different signal detectors, the Si – CCD and the InGaAs camera. A proof of concept for detecting a SBD with themal laser stimulation (TLS) is presented. Using a Si – CCD and up to 2000 s integration time, photon emission (PE) signals from a 2 μm × 2 μm test structure with a leakage current less than 1 nA are presented. With the InGaAs detector a localised SBD from a 2 μm × 2 μm test structure with a leakage current of 100 pA is shown. The detected SBDs have a resistance of 33 GΩ and 260 GΩ respectively thus the level of degradation is several orders of magnitude lower compared to a hard breakdown (HBD). Up to now it was only possible to localise defects at higher levels of degradation. Due to the high energy at these levels, original defect signatures for SBD are usually destroyed. To better control the process of degradation, a way to nearly freeze the degradation process is shown. This method was used to detect a 1 nA leakage current of a 2 μm × 2 μm structure with a resistance of 35 GΩ using optical beam induced resistance change (OBIRCH) which is a similar contactless fault isolation (CFI) method to TLS. The presented SBD localisations allow to plan accurate physical preparations for the first time. Physical analysis of PEM localised SBD and HBD have been performed and compared. Possibilities to further improve the presented SBD detection levels are discussed for OBIRCH. Limitations for PEM with Si – CCD and InGaAs detectors as a CFI for SBDs are discussed.